2017
DOI: 10.2174/1389450118666161205125548
|View full text |Cite
|
Sign up to set email alerts
|

Is Metformin a Therapeutic Paradigm for Colorectal Cancer: Insight into the Molecular Pathway?

Abstract: Colorectal cancer (CRC) remains one of the major leading causes of cancer related morbidity and mortality. Apart from the conventional anti-neoplastic agents, metformin, a biguanide anti-diabetic agent, has recently found to have anti-cancer property. Several studies observed the effect of metformin towards its anti-cancer effect on colon or colorectal cancer in diabetic patients. However, only a few studies showed its effect on colorectal cancer in relation to the non-diabetic status. The present review aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Mammalian target of rapamycin (mTOR) is also a serine/threonine protein kinase that regulates cell growth by integrating nutrient and growth factor signaling (11). Numerous studies have indicated that rapamycin may inhibit the proliferation of colorectal cancer cells in vivo and in vitro , and it has been suggested that the mTOR pathway is activated in patients with colorectal cancer (12,13). Therefore, targeting AMPK and mTOR signal pathways may be a promising protective strategy for management of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian target of rapamycin (mTOR) is also a serine/threonine protein kinase that regulates cell growth by integrating nutrient and growth factor signaling (11). Numerous studies have indicated that rapamycin may inhibit the proliferation of colorectal cancer cells in vivo and in vitro , and it has been suggested that the mTOR pathway is activated in patients with colorectal cancer (12,13). Therefore, targeting AMPK and mTOR signal pathways may be a promising protective strategy for management of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer has been reported to be one of the most common malignant tumors in the digestive system, and has high morbidity and mortality rates ( 1 , 2 ). A large number of studies have shown that dietary habits, induced inflammation and other factors such as genetic mutations can lead to the occurrence of colorectal cancer ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are evidence in vitro and in vivo studies that metformin has been considered a cancer chemotherapeutic agent. 4,5 Many clinical trials have been performed to investigate the inhibitory effects of metformin alone or in combination with other drugs on various cancers. Currently, two major pathways are recognized as the main ways in which metformin exerts its antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Metformin is currently used extensively in the treatment of type 2 diabetes mellitus (T2DM), but there is potential for additional indications in many other diseases, such as inflammatory disorders and cancers. [4][5][6][7] Epidemiological studies revealed an association between the use of metformin and decreased incidence of many types of cancers. 8,9 Diabetic patients taking metformin showed a decreased incidence of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%